Polyunsaturated Fatty Acid Content May Be Increased in the Milk of Women with Pregnancy-Associated Breast Cancer. (November 2014) - Qin, Wenyi; Raatz, Susan; Zhang, Ke K.; Rosenberger, Thad A.; Sauter, Edward R.
Background: Pregnancy-associated breast cancer (PABC) is aggressive and difficult to diagnose. High intake of most types of dietary fat is thought to increase breast cancer risk; however, results in humans supporting this premise remain equivocal. Fatty acid (FA) concentrations in the body comprise both dietary intake and endogenous FA production. Most assessments of FA levels have been performed on blood, with little information on the effect of FA levels in breast milk on PABC risk. Objective: This study aimed to determine if FA concentrations in the milk from women diagnosed with breast cancer while nursing were different in the cancer-containing breast and opposite breast. Methods: We quantified 16 long-chain FA and soluble FA synthase (sFAS) enzyme levels from 4 women diagnosed with PABC, comparing results from the cancer-containing breast to those from the normal breast. Results: Fatty acid concentrations consistently exceeded and trended higher ( P < .10) in each cancer-containing breast for 20:4n-6 (arachidonic acid [AA]), 20:5n-3 (eicosapentaenoic acid [EPA]), and 22:5n-6 (docosapentaenoic acid [DPA]). Soluble FA synthase levels were similar in the cancer-containing and normal breasts. Conclusion: Breast milk concentrations of AA, EPA, and DPA increased in the cancer-containing breast of women with PABC. This increase was not associated with higher sFAS levels.